Readers' guide to periodical literature 2009 - 20160731 frey50 (New York H. W. Wilson, 2010)
This is a cumulative author-subject index to English language periodicals of general interest. The main body of the Index consists of subject and author entries to periodical articles arranged in one alphabet. In addition there is a listing of citations to book reviews following the main body of the Index.
This volume includes indexing from December 19, 2008 - December 18, 2009. It supersedes the paper issues of Readers' Guide for Mary 2009 (Vol. 109 No. 1) thorugh February 2010 (Vol. 109 No. 12)
Keywords: Periodical literature - author index - 2009. -- Periodical literature - subject index - 2009.